Quantum Oscillations in the Anomalous Phase in Sr3Ru2O7 - Mercure, Jean-Francois (2009)
We report measurements of quantum oscillations detected in the putative nematic phase of Sr3Ru2O7. Improvements in sample purity enabled the resolution of small amplitude de Haas--van Alphen (dHvA) oscillations between two first order metamagnetic transitions delimiting the phase. Two distinct frequencies were observed, whose amplitudes follow the normal Lifshitz-Kosevich profile. Variations of the dHvA frequencies are explained in terms of a chemical potential shift produced by reaching a peak in the density of states, and an anomalous field dependence of the oscillatory amplitude provides information on domains.